Understanding and Adoption of Internet Banking: Nepalese Perspective - Ghimire, Binod; Rai, Bharat; Dahal, Rewan Kumar (KMC Research Journal, 2022)
The main objective of this study is to ascertain the elements that lead to the adoption of internet banking. By examining customers’ viewpoints, this research seeks to provide valuable insights into the fundamental determinants of this technological transition. A questionnaire survey was done among 398 banking customers in the Kathmandu Valley. The banking sector is currently experiencing a notable shift as a result of developments in telecommunications and information technology. These developments are facilitating transformative transformations through the introduction of novel distribution channels and the enhancement of banking value systems. These factors encompass the cost reduction, acceleration of service delivery, expansion of market reach, and enhancement of overall customer service quality. From a consumer's perspective, internet banking has the potential to reduce service prices and provide users with the ability to effortlessly manage their accounts at any time and from any location. The research findings have identified that security and trust as the most influential factors that lead customers' adoption towards internet banking, so bank managers should develop strategies to enhance overall service quality of internet banking services by delivering customized and quick financial services that help in meeting international standards with promising internet banking products and design.